Simplification of biochemical models: a general approach based on the analysis of the impact of individual species and reactions on the systems dynamics - Surovtsova, Irina; Simus, Natalia; Hübner, Katrin; Sahle, Sven; Kummer, Ursula (BMC systems biology, 2012)
Given the complex mechanisms underlying biochemical processes systems biology researchers tend to build ever increasing computational models. However, dealing with complex systems entails a variety of problems, e.g. difficult intuitive understanding, variety of time scales or non-identifiable parameters. Therefore, methods are needed that, at least semi-automatically, help to elucidate how the complexity of a model can be reduced such that important behavior is maintained and the predictive capacity of the model is increased. The results should be easily accessible and interpretable. In the best case such methods may also provide insight into fundamental biochemical mechanisms.